Vesicle Pools: Lessons from Adrenal Chromaffin Cells - Stevens, David R.; Schirra, Claudia; Becherer, Ute; Rettig, Jens (Frontiers in Synaptic Neuroscience, 2011)
The adrenal chromaffin cell serves as a model system to study fast Ca2+-dependent exocytosis. Membrane capacitance measurements in combination with Ca2+ uncaging offers a temporal resolution in the millisecond range and reveals that catecholamine release occurs in three distinct phases. Release of a readily releasable (RRP) and a slowly releasable (SRP) pool are followed by sustained release, due to maturation, and release of vesicles which were not release-ready at the start of the stimulus. Trains of depolarizations, a more physiological stimulus, induce release from a small immediately releasable pool of vesicles residing adjacent to calcium channels, as well as from the RRP. The SRP is poorly activated by depolarization. A sequential model, in which non-releasable docked vesicles are primed to a slowly releasable state, and then further mature to the readily releasable state, has been proposed. The docked state, dependent on membrane proximity, requires SNAP-25, synaptotagmin, and syntaxin. The ablation or modification of SNAP-25 and syntaxin, components of the SNARE complex, as well as of synaptotagmin, the calcium sensor, and modulators such complexins and Snapin alter the properties and/or magnitudes of different phases of release, and in particular can ablate the RRP. These results indicate that the composition of the SNARE complex and its interaction with modulatory molecules drives priming and provides a molecular basis for different pools of releasable vesicles.